Are intranasal corticosteroids beneficial for the treatment of acute sinusitis?. Issue 9 (September 2015) - Lazzopina, Peter; Mounsey, Anne
Abstract : Evidence‐Based Answer : About 10% more patients with acute sinusitis who use intranasal corticosteroids (INCS) will have complete or partial improvement than patients given placebo (SOR: A, meta‐analysis). Patients who receive INCS therapy and antibiotics may have better outcomes than those given antibiotics alone (SOR: C, conflicting RCTs of INCS and various antibiotics).